Aluminium nitride (AlN) as buffer layer for deposition of gallium nitride (GaN) thin films on silicon substrates using magnetron sputtering technique - Tahan, Muliana (2021)
Group III-nitrides semiconductors composed of gallium nitride (GaN), Indium nitride (InN), and aluminium nitride (AlN) had found use in broad technologies especially in optoelectronic and power devices. The main issues that limit the performance of GaN-based ultraviolet light-emitting diodes (UV-LEDs) are difficult to achieve highly crystalline GaN because lack of suitable substrates available and needed for high-temperature deposition process. Hence, the present research is focused on the enhancement of AlN as a buffer layer for the deposition of GaN thin films on Si substrate at low-temperature process using radio frequency RF magnetron sputtering. The function of AlN buffer layer is to reduces the lattice mismatch between the heterostructure of the thin films and its substrate. Firstly, the parameters such as type of sputtering used, target to substrate distance, deposition time, discharged power, and argon flow rate were varied to obtain high crystalline structure on AlN thin films. After AlN preferred crystal orientation structure obtains, GaN will be deposited on the top of it. The effect of thick and thin buffer layer to the GaN will be studied to see which will provide the lowest resistivity and high n-type carrier concentration for the GaN thin films. The parameter to obtain AlN high crystallinity structure is 200 W of discharged power, 120 min deposition time, 5 mTorr working pressure, and 100: 50 sccm of Ar to N flow rate. This is because, this parameter yield AlN (002) preferred orientation with full width at half maximum (FWHM) of 0.3838 and crystallite size 21.7712 nm, 186.73 nm thickness, and lowest surface roughness of 5.825 x101 nm. The deposition of GaN using 40 W on thick AlN buffer layer revealed that the electrical properties obtain are N-type carrier, low resistivity which is 1.025x10-5 Ω∙m, and high carrier concentration, 2.330x1024 m-³. These properties are comparable with previous literature to be suitable for realization of UV-LED even though using low-temperature processes and unconventional substrate.